Sociological and Islamic Legal Analysis of Sirri Marriage and Marriage Registration among Santri in Indonesia - Vina Tarsyihul Ulfah; Dzulfikar Rodafi; Shofiatul Jannah (KURAS Institute, 2025)
This study highlights the practice of unregistered marriage (sirri marriage) and marriage registration among students of the Salafiyah ad-Damanhuri Islamic Boarding School, viewed from a sociological and Islamic legal perspective. This research is an empirical legal study at the Salafiyah ad-Damanhuri Islamic Boarding School, using unstructured observation and field interviews with respondents, informants, and sources as data collection techniques, data collection through observation and interviews, then analyzed using the interactive analysis model of Miles, Huberman, and Sadanana. The results of this study indicate that in practice, marriages at the Salafiyah ad-Damanhuri Islamic Boarding School are carried out with the female guardian authorizing the kiai to marry his daughter, accompanied by the presence of the guardian and witnesses so that it is religiously valid, but it is still classified as unregistered marriage in the perspective of positive law. The main motivation for carrying out the unregistered marriage is the desire to obtain blessings (tabarrukan). The students register their marriages after the unregistered marriage by performing tajdid nikah at the KUA. Tabarrukan in the marriage contract is permitted, but marriage registration remains essential. The most appropriate method to restore legal recognition of a sirri ‘secret’ marriage is through the marriage confirmation mechanism, ensuring that the marriage is recognized from the outset.